2009
DOI: 10.1093/nar/gkp569
|View full text |Cite
|
Sign up to set email alerts
|

Differences between Ca 2+ and Mg 2+ in DNA binding and release by the SfiI restriction endonuclease: implications for DNA looping

Abstract: Many enzymes acting on DNA require Mg2+ ions not only for catalysis but also to bind DNA. Binding studies often employ Ca2+ as a substitute for Mg2+, to promote DNA binding whilst disallowing catalysis. The SfiI endonuclease requires divalent metal ions to bind DNA but, in contrast to many systems where Ca2+ mimics Mg2+, Ca2+ causes SfiI to bind DNA almost irreversibly. Equilibrium binding by wild-type SfiI cannot be conducted with Mg2+ present as the DNA is cleaved so, to study the effect of Mg2+ on DNA bindi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
34
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(35 citation statements)
references
References 49 publications
1
34
0
Order By: Relevance
“…Also, according to the XPS results discussed later, the phosphate group was selected here to represent the reactive site in the plasmid DNA. Although DNA bases could also be involved in the interaction, we focused on the DNA phosphate backbone as the main reactive site since Ca 2+ was reported to facilitate enzyme (protein)–DNA binding mainly through the phosphate backbone (Bellamy et al, 2009). Moreover, the binding of protein or polysaccharide to DNA bases only occurs under certain conditions; i.e., proteins bind to the DNA bases mainly via specific protein–DNA interaction involving base pairs of the cognate operator sequence (Kalodimos et al, 2004), and polysaccharides bind to DNA bases at high concentrations (Tajmir-Riahi et al, 1994).…”
Section: Methodsmentioning
confidence: 99%
“…Also, according to the XPS results discussed later, the phosphate group was selected here to represent the reactive site in the plasmid DNA. Although DNA bases could also be involved in the interaction, we focused on the DNA phosphate backbone as the main reactive site since Ca 2+ was reported to facilitate enzyme (protein)–DNA binding mainly through the phosphate backbone (Bellamy et al, 2009). Moreover, the binding of protein or polysaccharide to DNA bases only occurs under certain conditions; i.e., proteins bind to the DNA bases mainly via specific protein–DNA interaction involving base pairs of the cognate operator sequence (Kalodimos et al, 2004), and polysaccharides bind to DNA bases at high concentrations (Tajmir-Riahi et al, 1994).…”
Section: Methodsmentioning
confidence: 99%
“…EMSAs are typically used to probe equilibrium biomolecular binding, since two bound species would typically propagate differently than either separately, and is therefore important in the field of genomic expression 25,26 . Beyond equilibrium binding, EMSAs have also been used to measure dissociation kinetics 2735 . In addition, relative binding constants between competing ligands, orders of reactions, rate constants, and Arrhenius parameters can be measured using EMSAs 28 .…”
Section: Introductionmentioning
confidence: 99%
“…In some cases, EMSAs have also assisted in deducing reaction mechanisms 30 and the presence of reactive intermediates 33 . Variability in binding efficiencies between certain mutant and wild-type enzymes have been discerned by EMSAs 27 . Certain short-lived transient protein–DNA complexes can persist for hours in a polyacrylamide gel matrix during EMSAs 31 ; this persistence likely arises from cage effects caused by the gel matrix that strongly reduce the rate of decomplexing of such long biomolecules 29 .…”
Section: Introductionmentioning
confidence: 99%
“…Ca 2+ is a well-known analogue for Mg 2+ that contributes to the DNA binding specificity of Exo III for its endonuclease function. 32 Previous reports have demonstrated that in the presence of Ca 2+ , Exo III displays only 7 ± 2% of its normal endonucleolytic activity at C–C mismatched 5′ abasic sites relative to its activity at a matched C–G pair. 27 In order to maximize SNP discrimination, we first optimized the concentration of Ca 2+ in the system.…”
mentioning
confidence: 96%